A field observation on the philosophy of teaching Islamic and Arabic studies - Yaakub, Muhamadul Bakir (David Publishing Company, 2009)
Implementation of educational policy in designing curriculum details stands as a basis of conceptual educational practice. It is for sure involved time and space factors to become comprehensive and constructive, especially for teaching Islamic and Arabic studies within modern educational challenges where its uniqueness values in nature should be remained untouched, while its methodological approaches should be updated and dynamic in addressing the peculiarity of modern society increasingly. Consequently, it’s application and implementation in needs of some re-activation and adjustment to become more effective, productive and relevant. Popular and authorizations beliefs regarding educational contain have resulted in de facto Islamic and Arabic studies which largely reflect politically, rather than academically, realistically and effectively. In such a situation, it is vital to analyze the development of these policies and their implementation at a higher education.